2018
DOI: 10.3389/fmicb.2018.01231
|View full text |Cite
|
Sign up to set email alerts
|

The Fecal Microbiota in the Domestic Cat (Felis catus) Is Influenced by Interactions Between Age and Diet; A Five Year Longitudinal Study

Abstract: In humans, aging is associated with changes in the gastrointestinal microbiota; these changes may contribute to the age-related increase in incidence of many chronic diseases, including Type 2 diabetes. The life expectancies of cats are increasing, and they are also exhibiting the same types of diseases. While there are some studies investigating the impacts of diets on gastrointestinal microbiota in young cats, the impacts of aging in older cats has not been explored. We followed a cohort of related kittens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 53 publications
5
26
0
2
Order By: Relevance
“…In addition, the species composition of Lactobacillus was only found in preweaning and young groups but not in aged and senile cats, suggesting that Lactobacillus species may be not as important for cat health as in the case of humans and dogs. A similar conclusion was found in another longitudinal study, which did not identify Bifidobacteria in young cats but demonstrated similar Lactobacilli abundance in cats at different ages (8-260 weeks) using the 16S rRNA gene-based method (Bermingham et al, 2018). In this study, the most dominant group in young cats that were fed kibbled diets was an unclassified Peptostreptococcaceae (22.5%), whereas in older cats fed with the same diet, the most dominant group was Prevotella (29.7%).…”
Section: Factors Influencing Microbiota In Healthy Cats Age Gender supporting
confidence: 86%
“…In addition, the species composition of Lactobacillus was only found in preweaning and young groups but not in aged and senile cats, suggesting that Lactobacillus species may be not as important for cat health as in the case of humans and dogs. A similar conclusion was found in another longitudinal study, which did not identify Bifidobacteria in young cats but demonstrated similar Lactobacilli abundance in cats at different ages (8-260 weeks) using the 16S rRNA gene-based method (Bermingham et al, 2018). In this study, the most dominant group in young cats that were fed kibbled diets was an unclassified Peptostreptococcaceae (22.5%), whereas in older cats fed with the same diet, the most dominant group was Prevotella (29.7%).…”
Section: Factors Influencing Microbiota In Healthy Cats Age Gender supporting
confidence: 86%
“…Inherent in the outbred population of cats included in this study were numerous variables having potential impact on the microbiota including differences in age, breed, sex, clinical signs of diarrhea, and treatments administered [ 34 , 37 , 40 , 55 , 56 ]. Additional influences that were unknown for these cats include differences in diet, environment, comorbidities, or co-infections [ 35 , 36 , 38 , 56 58 ]. While these variables have a demonstrated impact on the fecal microbiota in studies controlling for their effects, their impact in this large, cross-sectional study population was not found to be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Another bacterium known to produce butyrate from protein sources is Fusobacterium varium (31), which was more abundant in a group of dogs fed meat-based raw diets for at least 1 year, suggesting an adaptation of the microbiome to the long-term diet (24). In addition, members of the Fusobacteriaceae family have been found to be more abundant in other carnivore species [cats: (18,32), wolves: (33,34), other carnivora: (17,35)], and dogs fed raw diets (19,23,36).…”
Section: The Effect Of Dietmentioning
confidence: 99%